2023
DOI: 10.1097/iae.0000000000003897
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Demographic Disparities in United States Emergency Department Visits in Patients With Rhegmatogenous Retinal Detachment

Abdulla R. Shaheen,
Noy Ashkenazy,
Prashanth G. Iyer
et al.

Abstract: Background/Purpose: Within the evolving landscape of healthcare in the United States (US), delineating the demographic nuances and financial implications of emergent conditions, such as rhegmatogenous retinal detachment (RRD), is paramount. This study seeks to analyze the demographic and hospital billing amount/cost of service disparities in RRD visits to emergency departments (EDs) nationwide. Methods: We conducted a retrospective, cross-sectional, pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…1.75-8.47; P = .001). 2 Many EDs do not have retina surgeons on staff or on call, and so many people then need to be referred to a retina surgeon after their visit to the ED. However, it has been reported that a quarter of patients presenting to the ED with an ophthalmic condition are lost to follow-up, with a higher rate of loss to follow-up among patients that have Medicaid or are uninsured compared with those with commercial insurance.…”
mentioning
confidence: 99%
“…1.75-8.47; P = .001). 2 Many EDs do not have retina surgeons on staff or on call, and so many people then need to be referred to a retina surgeon after their visit to the ED. However, it has been reported that a quarter of patients presenting to the ED with an ophthalmic condition are lost to follow-up, with a higher rate of loss to follow-up among patients that have Medicaid or are uninsured compared with those with commercial insurance.…”
mentioning
confidence: 99%